1960
DOI: 10.1172/jci104034
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Storage and Excretion of Sulfobromophthalein Sodium in the Dog *

Abstract: The use of a halogenated phthalein dye for the investigation of hepatic function was first proposed by Rowntree, Hurwitz and Bloomfield (1) in 1913. Their technique required the measurement of the fecal excretion of phenoltetrachlorphthalein following its parenteral administration. However, it was subsequently shown by Rosenthal and White (2) that intravenously administered phenoltetrabromophthalein disulfonate (BSP) is removed from the blood almost exclusively by the liver and that the function of the liver m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
2
1

Year Published

1960
1960
1989
1989

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 6 publications
4
28
2
1
Order By: Relevance
“…The magnitude of the average estimated Tm in dogs (1.9 mg per minute per 10 kg) is consistent with previous observations in this laboratory (9,10), but is considerably lower than the Lm of 4.4 mg per minute per 10 kg estimated by Mason, Hawley and Smith (11). A possible explanation for this difference is that Mason and co-workers employed a correction for variation in plasma concentration which did not take the storage phenomenon into account.…”
Section: Toxicitysupporting
confidence: 92%
See 3 more Smart Citations
“…The magnitude of the average estimated Tm in dogs (1.9 mg per minute per 10 kg) is consistent with previous observations in this laboratory (9,10), but is considerably lower than the Lm of 4.4 mg per minute per 10 kg estimated by Mason, Hawley and Smith (11). A possible explanation for this difference is that Mason and co-workers employed a correction for variation in plasma concentration which did not take the storage phenomenon into account.…”
Section: Toxicitysupporting
confidence: 92%
“…In the case of another phthalein dye, I131-labeled rose bengal, an accumulation or "storage phase" is apparent in the curves obtained by external counting over the liver after intravenous injection (7), and high concentration within liver cells has been confirmed by radioautography (8). Although it has been suggested that accumulation of BSP may proceed until there is complete "saturation" of intrahepatic storage sites (4,9), more recent evidence indicates that the process tends toward an equilibrium state in which the quantity (and hence the concentration) of BSP in the liver is directly proportional to the concentration of dye in the surrounding plasma (10) storage capacity" (S) as the number of milligrams of BSP stored in the liver per milligram per 100 ml of plasma concentration. The value of S can be estimated by comparison of the rates of movement of BSP into the liver associated with different rates of change of plasma concentration (10).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the hepatic uptake and biliary excretion of Sulfbromophthalein (BSP) have been previously reported in man (Wheeler, Meltzer and Bradley, 1960;Barber-Riley, Goetzee, Richards and Thomson, 1961) and for a number of laboratory species including the dog (Brauer and Pessotti, 1950;Wheeler, Epstein, Robinson and Snell, 1960), the sheep (Gronwall and Cornelius, 1970;Tucker, Mitchell and Little, 1971), the rat (Klaassen and Plaa, 1967), and the rabbit (Lewis, 1950). However, similar data are not available for the pig; what previous studies there are have given incomplete data on serum clearance in the intact animal (Cysewski, Pier, Engstrom, Richard, Dougherty and Thurston, 1968;Baker, Cushieri and Hanson, 1974) or have been concerned with BSP handling by the isolated perfused pig liver (Ham, Pirola and Elmslie, 1969).…”
Section: Introductionmentioning
confidence: 98%